A Journey to a Global Scholar Identity: An Autoethnography of Agricultural and Extension Faculty’s Experiences - Lacey Roberts-Hill; Richie Roberts; T. Grady Roberts (Journal of International Agricultural and Extension Education, 2023)
Working in the academy can be a very rewording career, but more and more faculty and graduate students are considering non-academic careers. Understanding the career journey of faculty in academic positions working in international agricultural and extension education (AEE) could be insightful to better understand this niche discipline and be informative to other faculty and graduate students along their own journeys. This article explores the journeys of three faculty members in international AEE. We used an autoethnography to our stories. We are an assistant professor, an associate professor, and a professor. We conducted a focus group and then examined: (a) curriculum vitae, (b) scholarly research, (c) research statements, and (d) teaching philosophies. We found three themes in our journeys: (a) a forked path, (b) peaks and valleys, and (c) navigating beyond – to embrace our professional identities as global scholars in international AEE. Recommendations ae made for AIAEE and other international AEE scholars.
Keywords: career stages; autoethnography; scholar; research